The H2O20 FREEWAT participated approach for the Follonica-Scarlino aquifer case study. A common space to generate shared knowledge on the value of water - Positano, Pio; Nannucci, Marco (Acque Sotterranee - Italian Journal of Groundwater, 2017)
The "Follonica-Scarlino Aquifer" case study is run within the H2020 FREEWAT project by Regione Toscana as partner of an international consortium. FREEWAT aims at promoting water resource management by simplifying the application of the Water Framework Directive and other EU water related Directives. The tool used to reach this target is an open source and public domain GIS integrated modeling environment for the simulation of water quantity and quality in surface water and groundwater. The case study area is located in a coastal plain in the Southern part of Tuscany (Italy) and the aquifer system is affected by various issues: in particular, the numerical model created through FREEWAT platform was used to study the problem of aquifer over-exploitation . The deficit in quantity of the water resource is mainly caused by the huge industrial and agricultural abstractions, but drinking water supply during the summer season is also notable. The participatory approach, included in the FREEWAT project, became of crucial importance to gather the huge amount of data about the aquifer system and to create a shared knowledge about water resource. It was carried out through seven focus groups and led the stakeholders to reach an agreement about the scenarios to be explored with FREEWAT software platform. Focus Group 1 to 3 were used to identify the case study objectives. Focus Groups 4 to 6 allowed to assess the water management issues and select the scenarios. The community chose two of the four scenarios that came out from the focus group meetings. Simulations corresponding to these two scenarios have shown, the effectiveness of the proposed technical solutions for achieving the objectives set out in the River Basin Management Plan of the Northern Apennines District. At the end of the focus group cycle, useful suggestions and feedbacks came from stakeholders, to set up a new kind of water management. Some experts working for local industries expressed their interest in using the FREEWAT open source platform as professional modeling tool.